A Study of Panglima LaâÅt: An âAdat Institution in Aceh - Bustamam-Ahmad, Kamaruzzaman (Al-Jamiah Research Centre, 2017)
This article is about a brief history of Panglima LaâÅt Aceh and its current position along with Adat LaâÅt (customary law) among Acehnese community. It will look at relationship between Adat and presence of Panglima LaâÅtÂ (the Commanders of the Sea). To what extent we could say that there is a strong connection between the adat laot and Panglima LaâÅt? It is argued that this institution has been established for more than 400 hundred years by the Kingdom of Aceh. It is also said that adat laot is one of the oldest customary law in Aceh. This article consists three sections. After the introduction, it will discuss the history of Panglima LaâÅt in Aceh. The next section is about the current position of Panglima LaâÅt in Acehnese society. Here, the data will be focussed on the dynamics of fisher and their perpection toward the Panglima LaâÅt in different setting of research area. Finally, the examination of the revitalization of Panglima LaâÅt as formal institution in, especially the overlapping of the authority of adat institution, will be provided in final section.[Tulisan ini merupakan penjelasan mengenai hubungan Panglima Laâot dengan hukum adat Laâot ditengah masyarakat Aceh dewasa ini yang secara resmi pemerintah daerahnya menegakkan syariâah Islam. Sebagai salah satu institusi adat yang tertua sejak berdirinya kerajaan Aceh, Panglima Laâot dan adat Laâot mengalami dinamika yang luar biasa. Dengan mengambil studi kasus dibeberapa tempat yang berbeda, penulis menunjukkan bahwa formalisasi kembali institusi ini bukan hanya menjadi cara melestarikan warisan budaya, melainkan juga menjadi aparatus pemerintahan lokal yang mewakili masyarakat nelayan Aceh ditengah dinamika ekonomi politik lokal, regional dan internasional.]Â Â Â Â Â